1990
DOI: 10.1021/j100365a014
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of quadrupolar coupling constants, shielding tensor elements and the relative orientation of quadrupolar and shielding tensor principal axis systems for rubidium-87 and rubidium-85 nuclei in rubidium salts by solid-state NMR

Abstract: The spin lattice relaxation time, T , , quadrupolar coupling constant, and chemical shielding tensor elements of several for IH's. Typical relaxation times for 87Rb are in the range of 100-300 ms and 50-300 ms for 85Rb. The Q , values are in the range of 7-14 MHz for 85Rb and 3-1 1 MHz for 87Rb. A program was created to numerically simulate and fit experimental powder patterns for the &/2 central transition, where the principal axis systems (PAS) of the shielding and quadrupole tensors are not coincident. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 4 publications
4
80
1
Order By: Relevance
“…We here report small or intermediate quadrupole couplings (5,6) or (ii) the single-crystal 87 Rb NMR studies for RbClO 4 and Rb 2 SO 4 , highly distorted lineshape for the central transition when in particular for comparison of the parameters for the two larger quadrupolar couplings are operative (7,8). However, tensorial interactions with the corresponding values deterfor most quadrupolar nuclei, the CSA is a quite small interacmined recently from static and MAS NMR (2,3,7,8), tion and, unfortunately, the effect of the CSA on the spectral which showed some discrepancies. Combining the results of appearance can easily be eliminated or drastically reduced by MAS even at fairly low spinning speeds.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…We here report small or intermediate quadrupole couplings (5,6) or (ii) the single-crystal 87 Rb NMR studies for RbClO 4 and Rb 2 SO 4 , highly distorted lineshape for the central transition when in particular for comparison of the parameters for the two larger quadrupolar couplings are operative (7,8). However, tensorial interactions with the corresponding values deterfor most quadrupolar nuclei, the CSA is a quite small interacmined recently from static and MAS NMR (2,3,7,8), tion and, unfortunately, the effect of the CSA on the spectral which showed some discrepancies. Combining the results of appearance can easily be eliminated or drastically reduced by MAS even at fairly low spinning speeds.…”
Section: Introductionmentioning
confidence: 52%
“…The present work demonstrates that, for half-integer quadpowders have shown that the magnitudes of the two tensorial rupolar nuclei, the quadrupole-coupling and CSA tensors interactions as well as their relative orientation may be obmay conveniently be determined from single-crystal NMR tained from the lineshape of the central transition (1)(2)(3) or of the central transition for very small CSAs. 87 Rb (I Å 3 2 ) from a spectrum of all transitions (4).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…d 33 , and the relative orientation of EFG and chemical-shift tensors may also influence the 139 La NMR lineshape. [45,46] The EFG tensor is described by the nuclear quadrupolar coupling constant, C Q = eQV ZZ h À1 , where e is the elementary charge, Q is the nuclear quadrupole moment, and h is the Planck constant, and the asymmetry parameter, ), which is restricted to values between À1 and + 1. [47] The relative orientation of the EFG and chemical-shift tensors is defined by the Euler angles-a, b, and g-and thus a total of eight parameters describe the NMR spectra, theoretical examples of which are presented in Figure 1 Typical experimental 139 La NMR spectra of solid lanthanum(iii) coordination compounds at applied magnetic fields of 11.75 and 17.60 T can be found in Figures 2-5.…”
Section: Resultsmentioning
confidence: 99%
“…Sites of general symmetry do not obey these constraints resulting in more complex line shapes. [39] The relative orientation of both PAS is described by Euler angles α, β, and γ. We refer to the right handed rotation as R(αβγ) = R z (γ) R y (β) R z (α).…”
Section: Nmr Signal Line Shape Analysismentioning
confidence: 99%